The poly-ADP ribose polymerase-1/apoptosis-inducing factor pathway may help mediate the protective effect of electroacupuncture on early brain injury after subarachnoid hemorrhage. Issue 8 (22nd May 2020) - Lang, Shuhui; Yan, Xiaogang; Wang, Chunsheng; Wu, Yan; Liu, Xing; Ma, Chunxiang; Li, Yongju; Xia, Hechun
Abstract : Subarachnoid hemorrhage (SAH) is a clinically common, acute, critical cerebrovascular disease associated with high mortality. Here, we investigated the effects of electroacupuncture on early brain injury after SAH. We successfully established a Sprague–Dawley rat model of the SAH model, and randomly divided the rats into four groups: sham-operated group, SAH group, positive control group, and electroacupuncture group. Electroacupuncture effectively decreased the number of transferase UTP nick end labeling-positive cells and extent of DNA fragmentation compared with the control, indicating a decrease in apoptosis. Moreover, electroacupuncture decreased the expression of proteins involved in the poly-ADP ribose polymerase-1/apoptosis-inducing factor (PARP-1/AIF) pathway in vivo, and the difference was statistically significant ( P  < 0.05). Treatment with electroacupuncture resulted in a significant improvement in neurological function. It inhibited the increase in blood–brain barrier permeability by regulating the protein expression of matrix metalloproteinase-9, occludin, and claudin-5. Additionally, electroacupuncture limited the development of cerebral edema and microglial activation in early brain injury after SAH. In conclusion, electroacupuncture can ameliorate early brain injury after SAH, and this may occur via inhibition of the PARP-1/AIF pathway.